Implied Nowhere : Absence in Folklore Studies - Ingram, Shelley, 1979-; Richardson, Todd, 1975-; Mullins, Willow (Willow G.) (Book collections on Project MUSE., 2019)
"In Implied Nowhere: Absence in Folklore Studies, authors Shelley Ingram, Willow G. Mullins, and Todd Richardson talk about things folklorists don't usually talk about. They ponder the tacit aspects of folklore and folklore studies, looking into the unarticulated expectations placed upon people whenever they talk about folklore and how those expectations necessarily affect the folklore they are talking about. The book's chapters are wide-ranging in subject and style, yet they all orbit the idea that much of folklore, both as a phenomenon and as a field, hinges upon unspoken or absent assumptions about who people are and what people do. The authors articulate theories and methodologies for making sense of these unexpressed absences, and, in the process, they offer critical new insights into discussions of race, authenticity, community, literature, popular culture, and scholarly authority. Taken as a whole, the book represents a new and challenging way of looking again at the ways groups come together to make meaning. In addition to the main chapters, the book also includes eight "interstitials," shorter studies that consider underappreciated aspects of folklore. These discussions, which range from a consideration of knitting in public to the ways that invisibility shapes an internet meme, are presented as questions rather than answers, encouraging readers to think about what more folklore and folklore studies might discover if only practitioners chose to look at their subjects from angles more cognizant of these unspoken gaps."--Provided by publisher.